Jaba- complejo de desarrollo eco-ambiental: Plan parcial la Perla del Caribe borde bio-ambiental (2017)
Currently the Caribbean Region is considered one of the new engines of economic development in Colombia where it is intended to carry out a project that integrates the Caribbean coast, Santander and the north of Santander to build a sustainable and competitive mega region called The Caribbean Diamond and Santanderes, which seeks, the scale of major cities as focal points of development and coordination with their municipalities for the formation of a region free of all aspects, environmental, functional, economic, social and heritage. For this in particular case, the region of Magdalena and its capital, Santa Marta is worked from the environmental point of view, due to the multiple natural riches present in the region, which frame, the development route, real, to prosecute, the human capital, to protection and exploitation. of them, that today are in danger due to climate change and abandonment. Problems that generate the exhaustion of natural resources, the inadequacy of public services, climatic emergencies, migrations, unplanned developments; debts that make the region vulnerable.